Inter-Religious Tolerance in Kubu Raya (Analysis of Living Sunnah in Multicultural Societies) - Wajidi Sayadi; Syarifah Asmiati (Khatulistiwa, 2019)
The cycle of tolerance or harmony among religious adherents in Kubu Raya Regency has been established very well, there is no turmoil, friction and conflict, except when there are plans for the establishment and construction of houses of worship. Even then there were only pro-contra moments in the discourse, but all of them could be resolved and overcome with mutual understanding and mutual respect among religious people. This tolerance is an application from the Living Sunnah. Factors influence and encourage the creation of tolerance and harmony in life between religious communities in Kubu Raya Regency are managed by the Regional Government of Kubu Raya Regency, the Ministry of Religion, whose main task is to foster harmony between religious groups and facilitate various dialogue activities.